Exploring Anaesthesia Options in Chickens: Zoletil vs. Midazolam-Ketamine vs. Dexmedetomidine-Ketamine - Debbarma, Manasi; Bayan, Hitesh; Konwar, Bedanga; Sarma, Kalyan (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Various anaesthetics and sedatives have been used for balanced anaesthesia in birds. Careful selection and appropriate dosage are  required due to potential anatomical, physiological, and metabolic variations. This study was aimed to evaluate the effects of zoletil,  midazolam-ketamine, and dexmedetomidine-ketamine in chickens. Eighteen chickens were divided into three equal groups and received  one of the anaesthetic combinations by intramuscular injections: Group A: zoletil @ 15 mg/kg; Group B: midazolam @ 0.5 mg/kg and  ketamine @ 40 mg/kg and Group C: dexmedetomidine @ 5 µg/kg and ketamine @ 20 mg/kg. Clinical and physiological parameters were  evaluated. Group A had faster sedation time and shorter anaesthesia duration. Group A and C had moderate sedation but rough recovery,  while Group B had heavy sedation and smooth recovery. Group B had shortest recovery time. Weak pedal and abolished palpebral reflex  with closed eyelids were observed in all groups. Heart rate and respiration rate decreased significantly at 30 min in all groups. Cloacal  temperature decreased significantly in Group A and C at 30 min, then non-significantly at 60 min, while non-significant fluctuations were  observed in Group B. Midazolam-ketamine showed better anaesthetic outcome than zoletil or dexmedetomidine-ketamine in chickens.
Keywords: Chickens; Dexmedetomidine; Ketamine,; Midazolam; Zoletil.